Direito à memória e a Guerrilha do Araguaia: um estudo de requerimento de anistia nos governos de Dilma Rousseff e de Jair Bolsonaro, sob a perspectiva da Análise Crítica do Discurso. - Meneses, João Paulo Dias de (2023)
Human rights are social and historical achievements, protected by national and international organizations and norms. Brazil experienced severe human rights violations during the military dictatorship between 1964 and 1985, such as in the Araguaia Guerrilla. However, there is a growing wave of denial of rights violations during the last period of dictatorship in Latin American countries. It is perceived that this has led to an authoritarian discourse in society, among some social actors, with a tendency to justify the Amnesty Law (Law 6.683/79), which impairs the Transitional Justice processes. These discourses influence the interpretation of the Amnesty Law and, consequently, the decisions rendered by the Amnesty Commission. Under the scope of the right to memory, this work aims to study the decisions of the Araguaia Guerrilla from the Amnesty Commission of the Dilma and Bolsonaro governments, comparing them based on the theoretical-methodological agenda of Critical Discourse Analysis. It is a bibliographic and documentary research. The methodological and theoretical bases that guided this work are mainly Fairclough (2003, 2016), Benjamin (2016), Thompson (2018), and Dijk (2018), highlighting ideological strategies for maintaining or overcoming political discourse, in addition to disputes over discursive meanings. The critical analysis of the votes focused on the categories of sense of discourse: actional meaning, symbolic meaning, and identificational meaning. It was observed that with the analysis of actional meaning, the intertextual construction of narratives in the councilors' votes on amnesty requests allowed for the distortion of direct statements by those seeking amnesty. Regarding representational meaning, it was concluded that the Amnesty Commission's commissioners represented the Araguaia Guerrilla's social actors based on ideological filters corresponding to their governments. Concerning identificational meaning, it was inferred that depending on the governments, votes are aligned with building identities for applicants based on the power relations of social actors. Thus, the critical analysis of the councilors' decisions enabled the recognition of conflicting identities of applicants, representation of social actors, and ideological mechanisms aligned with the Dilma or Bolsonaro government, understanding that ideological discourses are used in the dispute and construction of narratives about the military dictatorship for the implementation or not of the right to memory. Therefore, the right to memory, depending on the political-ideological position of the government, contributes to the implementation of rights related to Transitional Justice. It is urgent to develop strategies for reading the past of the military dictatorship based on human dignity and human rights principles.